Wheldone Revisited: Structure Revision Via DFT-GIAO Chemical Shift Calculations, 1,1-HD-ADEQUATE NMR Spectroscopy, and X-ray Crystallography Studies - Rangel-Grimaldo, Manuel; Earp, Cody E; Raja, Huzefa A; Wood, Jared S; Mardiana, Lina; Ho, Kin Lok; Longcake, Alexandra; Williamson, R Thomas; Palatinus, Lukáš; Hall, Michael J; Probert, Michael R; Oberlies, Nicholas H (Journal of natural products, 2024)
Wheldone is a fungal metabolite isolated from the coculture of Aspergillus fischeri and Xylaria flabelliformis, displaying cytotoxic activity against breast, melanoma, and ovarian cancer cell lines. Initially, its structure was characterized as an unusual 5-methyl-bicyclo[5.4.0]undeca-3,5-diene scaffold with a 2-hydroxy-1-propanone side chain and a 3-(2-(1-hydroxyethyl)-2-methyl-2,5-dihydrofuran-3-yl)acrylic acid moiety. Upon further examination, minor inconsistencies in the data suggested the need for the structure to be revisited. Thus, the structure of wheldone has been revised using an orthogonal experimental-computational approach, which combines 1,1-HD-ADEQUATE NMR experiments, DFT-GIAO chemical shift calculations, and single-crystal X-ray diffraction (SCXRD) analysis of a semisynthetic p-bromobenzylamide derivative, formed via a Steglich-type reaction. The summation of these data now permits the unequivocal assignment of both the structure and absolute configuration of the natural product.
Keywords: Aspergillus; molekulární struktura; Crystallography, X-Ray; Molecular Structure; Xylariales; krystalografie rentgenová; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; lidé; Humans